Broadband complex dielectric constants of water and sodium chloride aqueous solutions with different DC conductivities - Midi, Nur Shahida (Wiley, 2014)
Broadband dielectric constant measurements in the frequency range between 40 Hz and 50 GHz of pure water, tap water, and sodium chloride aqueous solutions with different DC conductivities up to 5 S/m were conducted. The measurements were done using an impedance analyzer for the frequency range 40 Hz to 110 MHz and a vector network analyzer for 10 MHz to 50 GHz. The results show that the dielectric constant decreases with the increase in DC conductivity and is dependent on the frequency. The dielectric relaxation of water with a constant dielectric loss peak was also observed. The frequency dependence of the conductivity is also large.